Radio-Echo Sounding: Glaciological Interpretations and Applications - Robin, G. de Q. (Journal of Glaciology, 1975)
Abstract After a brief review of factors relevant to the propagation of radio waves in ice, problems of profiling the upper and bedrock surfaces of ice sheets are considered. These include deconvolution of echo traces and accurate navigation. Results already available not only provide knowledge of sub-ice geomorphology, but also confirm our general ideas on interaction of temperature and flow in large ice sheets. Difficulties encountered in the study of temperate glaciers appear to be due to irregular dielectric properties of the ice mass, which in turn suggest an irregular distribution of water. In the future, application of radio-echo methods should lead to more detailed knowledge of accumulation and ablation over ice masses, improve our understanding of temperatures at great depths in polar ice sheets, and give data on ice movement from central areas of ice sheets.